Optimization of Automatic Pressure Valve System Based on Sensors and Microcontroller For Industrial Secondary Water Tank - Edy syahputra saragih; Andri Ramadhan (INFOKUM, 2025)
The efficiency and reliability of water distribution systems in industrial environments are highly dependent on the stability of water pressure within secondary water tanks. This study presents the design and optimization of an automatic pressure valve system based on pressure sensors and a microcontroller to regulate and maintain stable pressure levels in an industrial secondary water tank. The system utilizes real-time data from pressure sensors to control the opening and closing of an electric valve through a programmed microcontroller, ensuring responsive and adaptive performance. A PID (Proportional-Integral-Derivative) control algorithm is implemented to fine-tune the valve actuation, thereby reducing pressure fluctuations and improving overall system efficiency. Experimental testing was conducted under various load conditions to evaluate system responsiveness, accuracy, and energy consumption. Results show that the optimized control system significantly improves pressure stability, reduces manual intervention, and enhances operational reliability. This research contributes to the advancement of smart fluid control technologies in industrial applications, promoting more sustainable and automated water management systems.